2018
DOI: 10.1159/000492054
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Environmental Tobacco Smoke and Prevalence of Atopic Dermatitis among Adolescents in Kuwait

Abstract: Background: This study aimed to (i) assess the prevalence of exposure to environmental tobacco smoke (ETS) at homes, (ii) assess the prevalence of atopic dermatitis and (iii) evaluate the association between ETS exposure and atopic dermatitis status among adolescents. Methods: During October 2015, a cross-sectional study design was implemented using a self-administered, modified version of the ISAAC (International Study of Asthma and Allergies in Childhood) questionnaire among students enrolled in nine high sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 19 publications
2
25
1
Order By: Relevance
“…According to a global study, the secondhand exposure to smoke in a closed environment was high in children (40%), women (35%), and men (33%) with variation between regions ranged from ≤ 13% in Africa to ≥ 50% in western Pacific region or eastern Europe region (Öberg et al 2011 ). In Kuwait, a study conducted on high-school students ( n = 746) revealed that the prevalence of environmental tobacco smoke at home was 54%, which is higher than that in our estimate (38.6%) (Abdualrasool et al 2018 ). Moreover, another study from Kuwait reported that 45.8% ( n = 3836) of middle-school students and 51.6% ( n = 1936) of high-school students were exposed to secondhand smoke at home (Ziyab et al 2020 ).…”
Section: Discussioncontrasting
confidence: 81%
“…According to a global study, the secondhand exposure to smoke in a closed environment was high in children (40%), women (35%), and men (33%) with variation between regions ranged from ≤ 13% in Africa to ≥ 50% in western Pacific region or eastern Europe region (Öberg et al 2011 ). In Kuwait, a study conducted on high-school students ( n = 746) revealed that the prevalence of environmental tobacco smoke at home was 54%, which is higher than that in our estimate (38.6%) (Abdualrasool et al 2018 ). Moreover, another study from Kuwait reported that 45.8% ( n = 3836) of middle-school students and 51.6% ( n = 1936) of high-school students were exposed to secondhand smoke at home (Ziyab et al 2020 ).…”
Section: Discussioncontrasting
confidence: 81%
“…The questionnaire was pre-tested on 20 high school students and modifications were made as needed. The questionnaire comprised 21 questions and took on average five minutes for its completion [17].…”
Section: Questionnairementioning
confidence: 99%
“…The study population, setting and design have been previously described elsewhere [17], and brie y outlined here. During October 2015, we conducted a cross-sectional study among high-school students in Hawally -one of the six Governorates of Kuwait to i) assess the prevalence of ETS exposure at home, ii) assess the prevalence of various allergic conditions including asthma and iii) evaluate the association between ETS exposure at home and self-reported asthma.…”
Section: Population Setting and Study Designmentioning
confidence: 99%
“…From the Ministry of Education's website, we obtained a list of schools located in Hawally Governorate. From this list of 10 schools for boys, 9 schools for girls and 44 private schools with co-education system, nine schools were selected as a sample of convenience, which included three public sector schools each for male and female students and three private schools with coeducation [17].…”
Section: Population Setting and Study Designmentioning
confidence: 99%
See 1 more Smart Citation